2011
DOI: 10.1063/1.3524337
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering an analytical gradient expression within a divide-and-conquer self-consistent field approach: Exact formula and its approximate treatment

Abstract: An analytical energy gradient formula for the density-matrix-based linear-scaling divide-and-conquer (DC) self-consistent field (SCF) method was proposed in a previous paper by Yang and Lee (YL) [J. Chem. Phys. 103, 5674 (1995)]. Since the formula by YL does not correspond to the exact gradient of the DC-SCF energy, we derive the exact formula by direct differentiation, which requires solving the coupled-perturbed equations while including the inter-subsystem coupling terms. Next, we present an alternative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…The reduction of scaling is a major problem in computational chemistry. For this purpose, a variety of quantum-mechanical methods has been developed based on fragmentation of large systems [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], whose relation has been introduced by Nagata et al [26] and discussed in more detail in the recent review [27].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of scaling is a major problem in computational chemistry. For this purpose, a variety of quantum-mechanical methods has been developed based on fragmentation of large systems [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], whose relation has been introduced by Nagata et al [26] and discussed in more detail in the recent review [27].…”
Section: Introductionmentioning
confidence: 99%
“…Forces have been derived for the method [250], though the choice of applying the divide and conquer approach to the total system force (rather than differentiating the divide and conquer energy) may lead to slight discrepancies between the force and energy gradients. A more recent study of forces [251] showed that it is possible, though time-consuming, to derive an exact gradient, and proposed another approximate solution.…”
Section: Divide and Conquermentioning
confidence: 99%
“…5. Such problems may occur because of difficulties controlling the error in the force evaluations 6,74 as atoms move across the local zone boundaries and as the electronic FIG. 6.…”
Section: B Molecular Dynamics Simulationmentioning
confidence: 99%